2016
DOI: 10.1038/nature17654
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic acceleration and the evolution of human brain size and life history

Abstract: Humans are distinguished from the other living apes in having larger brains and an unusual life history that combines high reproductive output with slow childhood growth and exceptional longevity1. This suite of derived traits suggests major changes in energy expenditure and allocation in the human lineage, but direct measures of human and ape metabolism are needed to compare evolved energy strategies among hominoids. Here we used doubly labelled water measurements of total energy expenditure (TEE; kcal day−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
217
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 221 publications
(222 citation statements)
references
References 25 publications
4
217
0
1
Order By: Relevance
“…These larger territorial needs for humans appear to be associated with larger daily energy budgets. Recent work by Pontzer and colleagues [30,31] has shown that humans are indeed the "high energy" apes. Using the doubly labeled water (DLW) technique to quantify total daily energy expenditure (TEE; kcal/day), they have shown that humans have systematically and significantly greater energy budgets than chimpanzees, gorillas, or orangs.…”
Section: Tool Use and Foraging Strategiesmentioning
confidence: 99%
“…These larger territorial needs for humans appear to be associated with larger daily energy budgets. Recent work by Pontzer and colleagues [30,31] has shown that humans are indeed the "high energy" apes. Using the doubly labeled water (DLW) technique to quantify total daily energy expenditure (TEE; kcal/day), they have shown that humans have systematically and significantly greater energy budgets than chimpanzees, gorillas, or orangs.…”
Section: Tool Use and Foraging Strategiesmentioning
confidence: 99%
“…Extreme encephalization, where brain size greatly deviates from a lineage's allometric relationship between brain and body mass, is rare [14]. In studies of highly encephalized primates, both hypotheses are hotly debated [10], with some studies favouring the direct metabolic constraints hypothesis [5,9], and others favouring the energetic trade-off hypothesis [6,15]. Further, due to a lack of comparative studies of & 2016 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that calorie expenditures of human beings are similar regardless of the extent of physical activity [16,17]. Although exercise is very important for human health, exercise is not an effective measure of reducing weight.…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%